Spatio-temporal distribution of financial/economic violence in a northeastern state of Brazil (Research, Society and Development, 2024)
The Ministry of Health defines economic-financial violence (FEV) as destructive actions or omissions of the aggressor that affect the emotional health and survival of family members. Thus, the objective of this research was to analyze the spatio-temporal distribution of FEV in the state of Bahia, Northeastern Brazil. An ecological, time series study (2010-2018) was conducted, using spatio-temporal analysis tools. As a result, we observed that most cases of FEV occurred among women and the chances of the occurrence are higher in households, in adults and the elderly, in addition, there was an increasing trend of cases among males. We identified a heterogeneous distribution in the Bahian territory suggesting the inexistence of a distribution pattern of violence. However, in the spatial-temporal analysis high risk clusters were observed in the south-central region of the state. This work made it possible to identify areas of risk for the occurrence of AFV, especially in the south-central region of Bahia. Besides characterizing the victimized population, such as adults and the elderly being the most likely to suffer this type of violence.